A Visual Geography of Chernobyl: Double Exposure. (7th January 2014) - Davies, Thom
Abstract This article investigates the memories and lived experiences of those who dwell in the deindustrial landscape of Chernobyl in north Ukraine. Taking a visual approach to an invisible issue, the article explores the use of photography as a research tool to examine the 'hidden spaces of everyday life' in the shadow of Chernobyl.1 The article finds that many people have suffered a 'double exposure': once from radiation and then again from the failures of the Ukrainian state. While these communities are exposed as "bare life"2 to the risk of nuclear pollution, they also contest official conceptions of radiation through local knowledge, shared memory, and informal activity. The article interrogates the complex ways people perceive, negotiate, and come to terms with the ever-present but unseen menace of radiation. Through these memories, images, and lived experiences of the marginalized, we can begin to make the invisible threat of radiation appear more tangible. Finally, the article provides a short discussion about the use of participant photography in researching the invisible.